DETERMINANTS OF THE LEVEL OF FARMER WELFARE IN INDONESIA - Syaputri, Febianti Danu; Azwardi, Azwardi; Sukanto, Sukanto (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
The majority of Indonesia’s plural population relies on agriculture as their main source of income. In Indonesia, the agricultural industry plays a key role in food security and economic expansion. Improving the welfare of farmers is crucial to achieve food sovereignty, domestic agriculture, and food production. This research aims to determine the effect of the food security budget, fertilizer subsidy budget and inflation on the level of farmer welfare through farmer terms of trade (NTP) in Indonesia. This study uses secondary data spanning 17 years from 2007 to 2023. The analysis technique used is multiple linear regression. The results of this study indicate that the food security budget and inflation variables do not have an influence on the farmer terms of trade. Meanwhile, the fertilizer subsidy budget variable has a significant influence on the farmer terms of trade. This means that any growth in the fertilizer subsidy budget will lead to an increase in the farmer terms of trade, indicating that the welfare of farmers is increasing.